Leaching behaviour of low-grade copper ore in the presence of organic acid - Yaras, Ali; Arslanoglu, Hasan (Taylor & Francis Ltd, 2018)
This study investigated the kinetics of copper leaching from malachite ore using formic acid as an organic leaching reagent. The analysis was carried out to determine the effect of the following parameters: particle size, acid concentration, leaching time, formic acid/malachite ratio, reaction temperature and stirring speed. Based on the experimental results, the optimum leaching parameters are as follows: particle size, +75-30 mu m; formic acid concentration, 0.4 molL(-1); leaching time, 90min; formic acid (volume)/malachite (weight) ratio, 10 mLg(-1); temperature, 25 degrees C; and stirring speed, 200 rev min(-1). Copper extraction was 70.25% under optimum experimental conditions. Furthermore, a kinetic model was used to indicate the effects of these parameters on the leaching of copper from malachite ore in formic acid solution. It was observed that the leaching process was controlled by film diffusion through a product layer. In conclusion, formic acid can be utilised as an organic leaching reagent in the leaching process of other ores that are similar in structure and composition to malachite.
Keywords: Low-grade copper ore; malachite; leaching; organic acid; shrinking core model